VASYL STEFANYK IN CZECHIA: LIFETIME PERCEPTION IN REWIEWS AND TRANSLATIONS - Bydnyi, Vasyl (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The paper traces the perception of Vasyl Stefanyk’s works in Czechia, from the fi rst mention of him by Ivan Franko in the monthly “Slovanský přehled” in 1898 to the obituaries of the writer, who passed away at the end of 1936. Th e research outlines the genre spectrum of Czech publications concerning Stefanyk’s works (translations; reviews in periodicals; scholarly, educational, and reference editions) and the circle of authors that paid attention to Stefanyk’s writings. In particular, it specifi es the authorship of A. Proházka’s and V. Prach’s works assigned by cryptonyms. Stefanyk’s writings aroused the interest of the authors representing various literary directions and groups: Czech Modernism (František Šalda), the decadent periodical “Moderní revue” (Arnošt Proházka), a group of anarchist rebels (Stanislav K. Neumann), and the Masaryk’s movement of ‘realists’. Th e decadents and ‘rebels’ even showed a special aff ection for the Ukrainian author, as they were the fi rst to translate him in their magazines and published the writer’s earliest and most complete lifetime Czech collection “Povídky” (“Stories”) in 1905. Th ere were fi ve Stefanyk’s books published in the writer’s homeland during his lifetime, but the biggest attention of the Czech translators was drawn to the collection “Th e Little Blue Book”, and among the short stories – “Th e News”, “He Committed a Suicide”, “Maple Leaves”, and “My Word”. Among well-known translators were Karel Rypáček, Jaroslav Rozvoda, and Rudolf Hůlka. Alois Koudelka, Jan Máchal, Vincenc Charvát published critical works exploring the expressionist style and existential issues of Stefanyk’s works. Czech critics oft en took guidance from the discourse on Stefanyk represented by I. Franko, B. Lepkyi, and Lesia Ukrainka. Perception of Stefanyk’s writings developed into an engaging study of the writer’s works in the institutionally branched and aesthetically diff erentiated cultural environment of Czechia in the interwar 20th century. Th is interest helped to establish a closer CzechUkrainian literary dialogue.